PENGARUH MEDIA KARTU KUARTET TERHADAP KEMAMPUAN MEMBACA SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS II UPT SDN BENTENG SELATAN NO 60 KEPULAUAN SELAYAR - Muzdalifah Arif , Nurul; Adiwijaya Latief , Syekh; Ayu Andhira , Desy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the Effect of Quartet Card Learning Media on the Reading Ability of Class II Students. This study uses a pre-experimental research method using a one group pretest-posttest design. This research was conducted at UPT SDN Benteng Selatan No. 60 Kepulauan Selayar. The subjects of this study were class II B students with a sample size of 25 people using a sampling technique using only the experimental group without a control group (comparison). The data analysis technique used in this study is descriptive data analysis and inferential data, namely normality testing and hypothesis testing. Based on the discussion and results of the study, the effect of Quartet card learning media on the reading ability of class II students, a conclusion was obtained that Quartet card learning media has an effect on students' reading ability. This is evidenced by the results of the posttest which has an average of 84.16, far different from the results of the pretest with an average value of 51.28. The results of this research hypothesis obtained tcount> ttable or 9.251 <2.0639 While the sig value (2-tailed) obtained 0.001 then 0.001 <0.05 so it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of quartet card learning media on the reading ability of class II students of UPT SDN Benteng Selatan No.60 Kepulauan Selayar.